On inadequacies in transferring concepts from one to another (linguistic sub)discipline - Dressler, Wolfgang U. (Yearbook of the Poznan Linguistic Meeting, 2016)
The paper discusses several methodological problems in the necessary (mostly metaphorical) transfer of concepts from one discipline (or subdiscipline) into another one, especially when interdisciplinary research demands mutual understanding in terms of translation and correspondence of concepts. After differentiating between multidisciplinarity, interdisciplinarity and transdisciplinarity, the first is rejected and it is pleaded that the second and third should be combined. Several adequate and inadequate transfers of concepts into linguistics are dealt with, especially in the areas of morphology and language acquisition. Successful transfer is characterised by the formal transfer of new terms and their easy adaptation to already existing linguistic conceptions, especially between subdisciplines. Most often, further important differentiations of a concept cannot be transferred from the original discipline but must be added as enrichments within linguistics itself. This may lead to a split-up of concepts in different subdisciplines of linguistics. The concepts discussed are regression, self-organization, complexity, transparency vs. opacity, figure and ground, top-down processing, default, input, grammaticalisation.